THE GEN-Z BIBLE: SLANG ALKITAB SEBAGAI JEMBATAN MISI BAGI GENERASI Z - Sulaiman, Benita (The Way: Jurnal Teologi dan Kependidikan, 2025)
Various surveys show that many Generation Z (Gen Z) admit to no longer attending church and are no longer affiliated with any church. One reason is that church services are no longer engaging. Church services are monotonous due to the lack of digital technology. Another obstacle is the use of slang in worship and the use of biblical slang. This study aims to describe the need for the use of biblical slang and its potential use in church services. This qualitative research uses library research and sociolinguistic methods. The results show the importance of using biblical slang in services attended by Gen Z. Churches also have the potential to provide space for services that use biblical slang.